2017
DOI: 10.1101/156984
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insular cortex sub-region-dependent distribution pattern of α-synuclein immunoreactivity in Parkinson’s disease and dementia with Lewy bodies

Abstract: The insular cortex is a heterogeneous and widely connected brain region. It plays a role in autonomic, cognitive, emotional and somatosensory functions. Its complex and unique cytoarchitecture includes a periallocortical agranular, pro-isocortical dysgranular, and isocortical granular sub-regions. In Parkinson's disease (PD), the insula shows α-synuclein inclusions in advanced stages of the disease and its atrophy correlates with cognitive deficits. However, little is known regarding its regional neuropatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
4
0
0
Order By: Relevance
“…This suggests that the remodeling of the newly seeded fibrils into LB-like inclusions of distinct morphologies is driven not only by the structure of the PFF seeds but also by neuronal cell type-dependent properties. These findings are consistent with the immunohistochemical-based studies that revealed that the morphology of the LBs varies according to their location in human brain tissues from PD and synucleinopathies (17,44,50,72,73). Last, at D21, the level of LN-like pathology detected in E83Q PFF-treated neurons was higher than that in the mouse PFF-treated neurons (Fig.…”
Section: The E83q Mutation Induced the Formation Of Lb Inclusions Tha...supporting
confidence: 91%
See 1 more Smart Citation
“…This suggests that the remodeling of the newly seeded fibrils into LB-like inclusions of distinct morphologies is driven not only by the structure of the PFF seeds but also by neuronal cell type-dependent properties. These findings are consistent with the immunohistochemical-based studies that revealed that the morphology of the LBs varies according to their location in human brain tissues from PD and synucleinopathies (17,44,50,72,73). Last, at D21, the level of LN-like pathology detected in E83Q PFF-treated neurons was higher than that in the mouse PFF-treated neurons (Fig.…”
Section: The E83q Mutation Induced the Formation Of Lb Inclusions Tha...supporting
confidence: 91%
“…Consistent with previous findings, in cortical neurons, both endogenous aSyn and seeding activity levels are much lower than in hippocampal neurons. Therefore, our data suggest that intrinsic cellular properties, other than the endogenous level of aSyn or its misfolded properties, contribute to the cellular vulnerability to LB pathology formation and maturation, as also suggested in human synucleinopathies (72,73). Together, our findings demonstrate that in the primary neuronal seeding model, human PFFs generated from E83Q aSyn could (i) overcome the reported species barrier (36,37) and (ii) enhance the capacity of the human PFFs to trigger the de novo formation of pS129-positive fibrils capable of converting into LB-like inclusions.…”
Section: The E83q-mutant Asyn Pffs Induce the Formation Of Lb-like In...supporting
confidence: 69%
“…This suggests that the remodeling of the newly seeded fibrils into LB-like inclusions of distinct morphologies is driven not only by the structure of the PFF seeds but also by neuronal-cell type-dependent properties. These findings are consistent with the immunohistochemicalbased studies that revealed that the morphology of the LBs varies according to their location in human brain tissues from PD and synucleinopathies (26,69,100,101,108,113). Finally, at D21, the level of LN-like pathology detected in E83Q PFFs-treated neurons was higher than that of the mouse PFF-treated neurons (Fig.…”
Section: The E83q Mutation Induced the Formation Of Lb-inclusions That Resemble Many Of The Features Of Some Bona Fide Lewy Body Pathologsupporting
confidence: 91%
“…Consistent with previous findings, in cortical neurons, both endogenous aSyn and seeding activity levels are much lower than in hippocampal neurons. Therefore, our data suggest that intrinsic cellular properties, other than the endogenous level of aSyn or its misfolded properties, contribute to the cellular vulnerability to LB pathology formation and maturation, as also suggested in human synucleinopathies (100,101). Altogether, our findings demonstrate that in the primary neuronal seeding model, human PFFs generated from E83Q aSyn could: 1) overcome the reported species barrier (53,54); and 2) enhance the capacity of the human PFFs to trigger the de novo formation of pS129-positive fibrils capable of converting into LB-like inclusions…”
Section: The E83q-mutant Asyn Pffs Induce the Formation Of Lb-like Inclusions In Primary Neuronssupporting
confidence: 69%